Distributional range extension of Hypostomus nigropunctatus Garavello, Britski & Zawadzki, 2012 (Siluriformes: Loricariidae): New record for Argentina - Burchardt, Pablo Agustin (2024)
Hypostomus nigropunctatus is a loricarid species distributed in the Río Iguazú basin in Brazil. We revised some specimens from the Arroyo Urugua-í basin, Misiones, Argentina, which, based on a morphological comparison, are corroborated to be H.nigropunctatus. These specimens expand the species´ known distributionfrom the Iguazú basinto the Urugua-í basin. Furthermore, this finding is the first record of this species in Argentina.